2019
DOI: 10.1038/s41598-019-48025-3
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrally Tunable Dielectric Subwavelength Grating based Broadband Planar Light Concentrator

Abstract: Energy consumption of buildings is increasing at a rapid pace due to urbanization, while net-zero energy buildings offer a green and sustainable solution. However, limited rooftop availability on multi-story buildings poses a challenge for large-scale integration of photovoltaics. Conventional silicon solar panels block visible light making them unfeasible to cover all the surfaces of a building. Here, we demonstrate a novel dielectric grating based planar light concentrator. We integrate this functional devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Such material characterization for light-matter interactions bears a high-relevance for photo conversion applications such as solar cells. In fact, recent work on windowintegrated PC concentrators [45,46] has shown to deliver both renewable power generation whilst allowing for spectral-tuning of the optical structure to allow for natural room lighting and reduced air conditioning load on a dwelling by designing photonic structures (e.g. high contrast gratings) to reflect the infrared spectrum (reducing heat load), yet transmitting the visible portion.…”
Section: Impact Of Thickness Of Ito Window Layer In the Performance C...mentioning
confidence: 99%
“…Such material characterization for light-matter interactions bears a high-relevance for photo conversion applications such as solar cells. In fact, recent work on windowintegrated PC concentrators [45,46] has shown to deliver both renewable power generation whilst allowing for spectral-tuning of the optical structure to allow for natural room lighting and reduced air conditioning load on a dwelling by designing photonic structures (e.g. high contrast gratings) to reflect the infrared spectrum (reducing heat load), yet transmitting the visible portion.…”
Section: Impact Of Thickness Of Ito Window Layer In the Performance C...mentioning
confidence: 99%
“…The Such material characterization for light-matter interactions bears a high-relevance for photo conversion applications such as solar cells. In fact, recent work on windowintegrated PC concentrators [45,46] has shown to deliver both renewable power generation whilst allowing for spectral-tuning of the optical structure to allow for natural room lighting and reduced air conditioning load on a dwelling by designing photonic structures (e.g. high contrast gratings) to reflect the infrared spectrum (reducing heat load), yet transmitting the visible portion.…”
Section: Impact Of Thickness Of Ito Window Layer In the Performance Cmentioning
confidence: 99%
“…In fact, recent work on window-integrated PC concentrators [45,46] has shown to deliver both renewable power generation whilst allowing for spectral-tuning of the optical structure to allow for natural room lighting and reduced air conditioning load on a dwelling by designing photonic structures (e.g., high contrast gratings) to reflect the infrared spectrum (reducing heat load) yet transmitting the visible portion. Indeed, in this study we found that interplay between material quality to solar cell performance can be extended, in principle, to high absorption atomically flat van-der Waals materials such as those belonging to the class of transition metal dichalcogenides (TMD) for light emission [47] and light detection [48,49].…”
Section: Impact Of Thickness Of Ito Window Layer In the Performance C...mentioning
confidence: 99%